Jeremy Coote & Anthony Shelton (eds.): Anthropology, Art, and Aesthetics - Raahauge, Kirsten Marie (Tidsskriftet Antropologi, 2019)
Jeremy Coote & Anthony Shelton (eds.): Anthropology, Art, and Aesthetics Anmeldes af Kirsten Marie Raahauge